2012 20th IEEE International Conference on Program Comprehension (ICPC) 2012
DOI: 10.1109/icpc.2012.6240483
|View full text |Cite
|
Sign up to set email alerts
|

Do static type systems improve the maintainability of software systems? An empirical study

Abstract: Abstract-Static type systems play an essential role in contemporary programming languages. Despite their importance, whether static type systems influence human software development capabilities remains an open question. One frequently mentioned argument for static type systems is that they improve the maintainability of software systems-an often used claim for which there is no empirical evidence. This paper describes an experiment which tests whether static type systems improve the maintainability of softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 15 publications
(15 reference statements)
4
65
1
Order By: Relevance
“…Finally, Kleinschmager et al performed an experiment on 33 subjects which combined repetitions of previous experiments (with Java and Groovy as languages) [15]. Among other tested hypotheses, it was confirmed that fixing type errors in a statically typed language is faster than corresponding fixes in a dynamically typed language, while no differences for fixing semantic errors was measured.…”
Section: Related Workmentioning
confidence: 94%
See 4 more Smart Citations
“…Finally, Kleinschmager et al performed an experiment on 33 subjects which combined repetitions of previous experiments (with Java and Groovy as languages) [15]. Among other tested hypotheses, it was confirmed that fixing type errors in a statically typed language is faster than corresponding fixes in a dynamically typed language, while no differences for fixing semantic errors was measured.…”
Section: Related Workmentioning
confidence: 94%
“…Consequently, using Eclipse would probably have been an advantage for Java developers and would have confounded the measurements: the intention of the experiment was to measure the impact of the language feature type system, not the maturity level of tool support. Hence, we decided to use a plain text editor with syntax highlighting, as has been done in previous experiments [15,27]. This custom editor permitted the user to compile programs, run applications, and execute test cases.…”
Section: Programming Languages and Environmentmentioning
confidence: 99%
See 3 more Smart Citations